Intermetatarsal Screw Fixation Reduced Intermetatarsal Angle Following Modified Lapidus Procedures. Issue 4 (November 2022) - Reed, Logan; Luque-Sanchez, Kevin S.; Awad, Shadi K.; Mihas, Alexander K.; Young, Sean M.; Patch, David A.; Johnson, Michael D.
Category: Midfoot/Forefoot Introduction/Purpose: The Modified Lapidus arthrodesis is a historically established surgical technique for treatment of hallux valgus, providing quality patient outcomes and reproducible results. Addition of a transverse first to second intermetatarsal screw spanning the base of the metatarsals in this procedure can increase stability. However, no study evaluates the radiographical parameters following application of this intermetatarsal screw fixation to procedures without first to second intermetatarsal screw fixation. The purpose of this study was to assess the quality of radiographic parameters between individuals receiving a first to second intertarsal screw fixation to those that did not receive intermetatarsal screw fixation following a non-saw cut Modified Lapidus procedure. Methods: A retrospective review was performed on 74 patients that underwent a Modified Lapidus arthrodesis between 2016- 2020 at a single institution. Preoperative indications for the procedure included first ray instability, first ray hypermobility, hallux abductovalgus, and metatarsal primus elevatus. Inclusion criteria consisted of skeletally mature patients undergoing non sawcut Modified Lapidus procedure. Patients that received the procedure due to a traumatic event or patients with concomitant second metatarsal arthrodesis were excluded. Review of patient's charts was performed. Basic demographics data, implant type, and radiographic parameters including intermetatarsal angle (IMA) and first metatarsal length were obtained from preoperative as well as postoperative films. Results: A total of 74 patients who underwent a Modified Lapidus arthrodesis were included in the study. A group of 43 patients received the Modified Lapidus arthrodesis with the addition of a first to second intermetatarsal screw fixation compared to a group of 31 patients who only received the Modified Lapidus arthrodesis procedure. The average IMA in all patients prior to surgery was 13°. The patients who received intermetatarsal screw fixation had significantly higher IMA reductions between preoperative and postoperative films than those who did not receive the intermetatarsal screw (-8.41° vs. -5.78°, p=.005). The difference in first metatarsal length on preoperative and postoperative films was less in patients who received the screw fixation but this was not statistically significant. Conclusion: The Modified Lapidus procedure is a commonly used procedure to treat hallux valgus. The results of this study found that the addition of a first to second intermetatarsal significantly reduced the IMA when compared to individuals who did not receive the screw construct. These findings will help surgeons further delineate if an intermetatarsal screw is required and how it will contribute to the radiographic parameters of interest.